The origin of sandstone boulder aprons along the escarpments of the Stołowe Mountains: are they all rockfall-derived? A new insight into an old problem using the CONEFALL 1.0 software - Duszyński, Filip; Migoń, Piotr; Strzelecki, Mateusz Czesław (Bulletin of Geography. Physical Geography Series, 2015)
A characteristic feature of sandstone-capped escarpments in the Stołowe Mountains is the occurrence of extensive boulder mantles which extend from the rock face to the footslope over distances of 300–500 m. The hypothesis implying rockfall as the process of boulder release from the rock face and subsequent transport is tested by means of Conefall 1.0 software, designed to simulate run-out zones of rockfalls. The actual extent of boulder mantles is much larger than the simulated extent, which casts doubt on the applicability of rockfall scenario. Alternative hypotheses are briefly discussed and it is concluded that a similar morphological effect can be achieved by in situ caprock disintegration and sub-caprock slope lowering and retreat.